Marc's mission - Willink, Jocko; Bozak, Jon (New York : Feiwel and Friends, 2018)
Marc hopes that his Uncle Jake can help him turn around his terrible summer, which he has to spend at camp with Nathan James, who is mean and annoying, while longing for a fancy new bike his parents will not buy him.
Keywords: United States. -- Navy. -- SEALs -- Juvenile fiction; United States. -- Navy. -- SEALs -- Fiction; Camps -- Juvenile fiction; Self-control -- Juvenile fiction; Uncles -- Juvenile fiction; Camps -- Fiction; Self-control -- Fiction; Uncles -- Fiction; JUVENILE FICTION / Social Themes / Adolescence